Locked in echoes: unveiling the dynamics of social media echo chambers and Hindu radicalization targeting Muslim youth in Delhi - Abdul Fahad; Siti Ezaleila Mustafa (Humanities & Social Sciences Communications)
Abstract The concept of a social media echo chamber is when someone is exposed to biased and personal media that ignores diverse viewpoints and opposing viewpoints. There are many underlying causes for the radicalization of Hindu youth in Delhi, and the problem is complex. An in-depth examination of Hindu nationalism, a political ideology that promotes the creation of a Hindu Rashtra predominantly focused on the supremacy of the upper caste, especially Brahmin principles, is imperative within the realm of development studies. The repercussions of the radicalization of Hindu youth in Delhi are particularly significant as a result of the aggressive actions against Muslims that have resulted from this ideology, which have induced a climate of dread and disquiet. Extremist organizations use echo chambers as a propaganda tool to indoctrinate youth. These virtual worlds reinforce pre-existing convictions by providing information that supports their ideology. This research investigates the subtleties of social media echo chambers to evaluate the radicalization of Hindus and its repercussions on the experiences of Muslim youth in Delhi. The goal of this study is to pinpoint the underlying mechanisms by which social media echo chambers facilitate the radicalization of Hindus and the targeting of Muslim youth.